Management of Continuous Positive Airway Pressure in the Newborn: Impact of Lecture-based Interactive Workshops on Training for Neonatal Intensive Care Nurses - Öznur Tiryaki; Nursan Cinar (Universidad de La Sabana, 2016)
Objectives: The aim of this study was to determine how training imparted via structured workshops related to management of continuous positive airway pressure in the newborn affects the knowledge of neonatal intensive care nurses. Methods: A group of nurses attended an interactive lecture-based workshop on management of continuous positive airway pressure in the newborn. The nurses in question had accepted an invitation to the presentation prior to the training event. Information on the participants' differentiating features was collected via a questionnaire prepared by the researchers themselves. An evaluation of the nurses' knowledge on the subject was performed through a multiple choice questionnaire (MCQ) prepared by the researchers in relation to the literature. After the MCQ was prepared, it was mailed to experts in Turkey (7 people) and experts from abroad (5 people), and their opinions were considered. In light of their suggestions, the MCQ was given its final form and the number of questions was set at 20. The MCQ consisting of 20 questions was answered by the participants before and after the interactive workshop. The participants were not informed as to whether or not the test would be repeated after the training. Results: Thirty-six nurses from the neonatal unit took part in the study. Each question in the MCQ was considered as one (1) point. The maximum possible score on the test was 20. There was a significant improvement in the mean test score after the lecture, when compared to the pre-lecture score (Mean = 19.6, SD=0.8 vs. Mean =13.1, SD=3.0, P<0.001). Conclusions: A lecture-based inter active workshop on management of continuous positive airway pressure in newborns helps to improve nurses' knowledge. It also helps to overcome deficiencies in nurse training.   DOI: 10.5294/aqui.2016.16.2.4